(untitled) (Baghdad Science Journal, 2018)
The present study is a hybrid method of studying the effect of plasma on the living tissue by using the image processing technique. This research explains the effect of microwave plasma on the DNA cell using the comet score application, texture analysis image processing and the effect of microwave plasma on the liver using texture analysis image processing. The study was applied on the mice cells. The exposure to the plasma is done by dividing the mice for four groups, each group includes four mice (control group, 20, 50, 90 second exposure to microwave plasma). The exposure to microwave plasma was done with voltage 175v and gas flow on 2 with room temperature; the statistical features are obtained from the comet score images and the textural features are calculated from the texture matrix energy measure. The result shows that the plasma has a clear effect on the DNA by reaper the damage cell and affecting the liver enzyme. The microwave plasma affected the ALP (Alkaline phosphatase) enzyme Alanine amino Transferase (ALT), Aspartate amino Transferase (AST) by decreasing their value with time exposure. This has been analyzed and studier by the textural analysis.